Das therapeutisierte Subjekt: Arbeiten am Selbst in Psychotherapie, Beratung und Coaching - Georg, Eva (transcript, 2020)
How does work on the self in counselling, coaching and psychotherapy work if the idea of the autonomous subject is neither the starting point nor the goal?